Examination of Gel Hand Sanitizer from Mangrove Leaves and Patchouli Oil Against Sthapylococcus Aureus - Fahreni Fahreni; Vivi Mardina; Indriaty Indriaty; Ramaidani Ramaidani (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
The development of hand sanitizers from a combination of mangrove leaves and patchouli oil has not yet developed in the world and Indonesia, though these two natural ingredients have antibacterial activity as a substitute for alcohol. It is known that many alcohol-based hand sanitizers can cause burning, irritation, dry skin, and cannot be used on wound skin. The purpose of this study was to develop an innovative hand sanitizer in the form of a gel from a combination of mangrove leaves extract and patchouli oil from Aceh. The samples of mangroves (Avicennia) leaves and Patchouli oil were collected from the Kuala Langsa Mangrove Forest and patchouli farmers in South Aceh. Staphylococcous aereus bacteria were obtained from the Laboratory of Universitas Sumatera Utara. This study used a completely randomized design (CRD) with three replications for the gel formulation. The study prepared four formulations namely K (-) as control without mangrove extract and patchouli oil, F-I contained 1g mangrove extract and 10mL patchouli oil, F-II contained 5g mangrove extract and 20mL patchouli oil, and F-III contained 10g mangrove extract and 30mL patchouli oil. Gel hand sanitizer formulations were test for antibacterial active using diffusion method against S. aereus. The data were analyzed using one-way ANOVA. The results of the gel hand sanitizer formulation showed inhibitory effect against S. aereus with the diameter zones of 12.6 mm, 21.33 mm, 19.61 mm and 25 mm for negative control, F-I, F-II, and F-III. The F-III formulation was found as the maximum formula to inhibit the growth of S. aereus.